Shopper Purchasing Trends at Small Stores on the Navajo Nation since the Passage of the Healthy Diné Nation Act Tax: A Multi-Year Cross-sectional Survey. Issue 5 (23rd March 2022) - Trujillo Lalla, Amber; George, Carmen; Bancroft, Carolyn; Edison, Tierra; Ricks, Audrey; Tabb, Kayla; Sandman, Sharon; Salt, Shine K; Curley, Cameron; de Heer, Hendrik "Dirk"; Curley, Caleigh A; Yazzie, Del; et al.
ABSTRACT: Background: In 2014, the Navajo Nation passed the Healthy Diné Nation Act (HDNA), which applies an additional 2% tax on unhealthy foods and beverages and a waiver of Navajo sales tax on healthy foods and beverages. However, the HDNA's impact on purchasing behavior has not been explored. Objectives: We assessed beverage and produce purchasing trends among shoppers at small Navajo stores between 2017 and 2019, shopper characteristics associated with buying water, and whether HDNA awareness was associated with purchasing behaviors. Methods: A total of 332 shoppers at 34 stores in 2017 and 274 shoppers at 44 stores in 2019 were surveyed to assess HDNA awareness and same-day purchasing of water, sugar-sweetened beverages (SSBs), fruits, and vegetables. Hypotheses were tested using chi-square analyses and multivariate analysis. Results: Water purchasing among respondents increased significantly from 2017 to 2019 (24.4% to 32.8%; P  = 0.03). Shoppers in 2019 were 1.5 times more likely to purchase water compared with 2017 (adjusted P = 0.01). There was a trend toward reduced SSB purchasing (85.8% in 2017, 80.3% in 2019, P  = 0.068), while produce purchasing remained unchanged over time, at approximately 17%. Shoppers were more likely to buy water if they relied on that store for the majority of their groceries ( P  = 0.006) and if they did not have their own transportation to get to the store ( P  = 0.004). Most shoppers (56.6%) were aware of the HDNA; of these, 35.6% attributed healthier habits to the HDNA, most commonly buying more healthy drinks (49.2%), fewer unhealthy drinks (37.7%), more healthy snacks (31.1%), and fewer unhealthy snacks (26.2%). Conclusions: Shopper habits at small stores located on the Navajo Nation have shifted towards healthier purchasing from 2017 to 2019. Shoppers who were aware of the HDNA reported purchasing more healthy and fewer unhealthy food and drinks as a result of this legislation. Abstract : Shoppers at Navajo stores bought healthier beverages in 2019 compared with 2017. These trends were partially attributed to the "junk food tax" and the tax waiver on healthy items.